157k views
4 votes
4> Solve by using Laplace transform: y'+5y'+4y=0; y(0)=3 y'(o)=o

User Bob Fanger
by
6.0k points

1 Answer

5 votes

Answer:


y=3e^(-4t)

Explanation:


y''+5y'+4y=0

Applying the Laplace transform:


\mathcal{L}[y'']+5\mathcal{L}[y']+4\mathcal{L}[y']=0

With the formulas:


\mathcal{L}[y'']=s^2\mathcal{L}[y]-y(0)s-y'(0)


\mathcal{L}[y']=s\mathcal{L}[y]-y(0)


\mathcal{L}[x]=L


s^2L-3s+5sL-3+4L=0

Solving for
L


L(s^2+5s+4)=3s+3


L=(3s+3)/(s^2+5s+4)


L=(3(s+1))/((s+1)(s+4))


L=\frac3{s+4}

Apply the inverse Laplace transform with this formula:


\mathcal{L}^(-1)[\frac1{s-a}]=e^(at)


y=3\mathcal{L}^(-1)[\frac1{s+4}]=3e^(-4t)

User Baper
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.